Herbicidas que Afectan el Proceso de Fotosíntesis - Almeida Sánchez, Benigno Xavier (2022)
Herbicides are chemical products, in their enormous integrity of synthetic origin, used in agriculture in order to minimize, interrupt or remove the development of unwanted plants, also known as weeds, on land that was or will be cultivated. For an herbicide to accomplish the task of maintaining control of weeds by harming their physiological and biochemical processes, it will have to penetrate inside the plants and move from the penetration sites to the place where it carries out its action. Most of the available herbicides interact with plant cells in ways that cause damage by interfering with the deployment of energy from sunlight. The mechanism of action, or site of action, of an herbicide is related to the specific metabolic pathway or specific biochemical site in the plant. All herbicides that inhibit photosynthesis to the degree of cytochrome QB of protein D1 stop photosynthetic electron transport. There is a clear division of herbicides that inhibit photosynthesis among which, according to experts, the following groups stand out; Group 1: triazines, substituted ureas and uracils, Group 2: Bipyridyls, Finally, group 3: triazoles. Triazines inhibit the transport of electrons in photosystem II, the damage they present is like leaf chlorosis or necrosis. Substituted Ureas: they work on photosynthesis and generate chlorosis, necrosis and death. If they are applied post-emergence, their action is contact. Bipyridyls: they have a high reducing potential which enables them to receive electrons from photosystem I. Triazoles: they inhibit the production of carotenoids, which is a substance that protects the chlorophyll molecule.